Deep Digital Flexor Contracture following Combined Tibial Plateau Levelling Osteotomy and Cranial Closing Wedge Ostectomy: A Case Report in a Dog - Price, Anya; Lopez, Daniel; Valenzano, Dominick; Frye, Christopher; Krotscheck, Ursula (VCOT Open, 2022)
This case report describes the use of a Z-plasty tenotomy and anastomosis to surgically lengthen the deep digital flexor (DDF) tendons of digits 2 to 5 of the pelvic limb in a 6-year-old male castrated Greyhound. The procedure was used to treat contracture of this tendon complex which developed after a series of complications secondary to proximal osteotomies utilized for the treatment of cranial cruciate ligament rupture. The dog was evaluated for lameness associated with left cranial cruciate ligament rupture and excessive tibial plateau slope; accordingly, a combined tibial plateau levelling osteotomy and cranial closing wedge ostectomy was performed. Postoperatively, the dog developed substantial DDF tendon contracture that led to severe digital hyperflexion and contributed to a non-weight bearing lameness. The dog received intensive rehabilitation therapy but failed to substantially improve; therefore, all of the weight-bearing left hindlimb DDF tendons were lengthened with a Z-plasty tenotomy and anastomosis followed by further rehabilitation. Follow-up evaluation 44 months postoperatively documented mild, intermittent left hindlimb lameness on gait observation and confirmed success of the Z-plasty procedure via ultrasonographic evaluation. Conservative treatment alone was unsuccessful in managing DDF tendon contracture in this dog. Z-plasty tenotomy and anastomosis of the DDF tendon allowed for return-to-acceptable function in this case.
Keywords: Z-plasty tenotomy; dog; deep digital flexor tendon contracture; TPLO complication